Expression of wild-type PtrIAA14.1, a poplar Aux/IAA gene causes morphological changes in Arabidopsis - Liu, Shanda; Hu, Qingnan; Luo, Sha; Li, Qianqian; Yang, Xiyu; Wang, Xianling; Wang, Shucai (Frontiers in Plant Science, 2015)
Aux/IAA proteins are transcriptional repressors that control auxin signaling by interacting with Auxin Response Factors (ARFs). So far all of the identified Aux/IAA mutants with auxin-related phenotypes in Arabidopsis and rice (Oryza sativa) are dominant gain-of-function mutants, with mutantions in Domain II that affected stability of the corresponding Aux/IAA proteins. On the other hand, morphological changes were observed in knock-down mutants of Aux/IAA genes in tomato (Solanum lycopersicum), suggesting that functions of Aux/IAA proteins may be specific for certain plant species. We report here the characterization of PtrIAA14.1, a poplar (Populus trichocarpa) homologue of IAA7. Bioinformatics analysis showed that PtrIAA14.1 is a classic Aux/IAA protein. It contains four conserved domains with the repressor motif in Domain I, the degron in Domain II, and the conserved amino acid signatures for protein-protein interactions in Domain III and Domain IV. Protoplast transfection assays showed that PtrIAA14.1 is localized in nucleus. It is unable in the presence of auxin, and it represses auxin response reporter gene expression. Expression of wild type PtrIAA14.1 in Arabidopsis resulted in auxin-related phenotypes including down-curling leaves, semi-draft with increased number of branches, and greatly reduced fertility, but expression of the Arabidopsis Aux/IAA genes tested remain largely unchanged in the transgenic plants. Protein-protein interaction assays in yeast and protoplasts showed that PtrIAA14.1 interacted with ARF5, but not other ARFs. Consistent with this observation, vascular patterning was altered in the transgenic plants, and the expression of AtHB8 (Arabidopsis thaliana Homeobox Gene 8) was reduced in transgenic plants.